Nanocarrier drug delivery system: promising platform for targeted depression therapy - Feng, Xiaoying; Jia, Ping; Zhang, Dingding (Frontiers in Pharmacology, 2024)
Depression is a chronic mental disorder characterized by persistent low mood and loss of interest.Treatments for depression are varied but may not be sufficient cure. Drug-based treatment regimens have drawbacks such as slow onset of action, low bioavailability, and drug side effects. Nanocarrier Drug Delivery Systems (NDDS) has received increasing attention for brain drug delivery since it assists the drug through the blood-brain barrier and improves bioavailability, which may be beneficial for treating depression. Due to the particle size and physicochemical properties of nanocarriers, it presents a promise to improve the stability and solubility of antidepressants, thereby enhancing the drug concentration. Moreover, ligand-modified nanocarriers can be taken as a target direct medicines release system and reduce drug side effects. The purpose of the present review is to provide an up-to-date understanding of the Nanocarrier drug delivery system and relevant antidepressants in different routes of ingestion, to lay a foundation for the treatment of patients with depression.